MORAL VALUES IN A MOVIE ENTITLED FROZEN BY JENNIFER LEE - Ericha Nataliana Nugraheni; Ch. Evy Tri Widyahening (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2022)
The objective of this research was to analyze the moral values which were described by the characters in “Frozen” movie. This research is classified as a qualitative research type using a descriptive approach. The data from this study comes from “Frozen” movie and dialogue. Then, in collecting data the researcher used documentation by watching the movie and reading the script. In analyzing data, the researcher used interactive data analysis by Miles and Huberman. To find the research's validity, triangulation data and triangulation theory were used to check validation for the data. The result of this research has demonstrated that there are moral values that could be found in the movie entitled Frozen, such as dishonesty, bravery, peace ability, confidence, loyalty, respect, love and affection, not selfish, kind and friendly, fair and human that depicted by the characters of Hans, Elsa, Anna, Kristoff, Olaf, and The King (Elsa’s and Anna’s father).Keywords: Moral Values, Frozen Movie, Descriptive Qualitative.